Primary Langerhans cell sarcoma in the urinary bladder: Case report and literature review - Wei, Yongbao; Hong, Huaishan; Huang, Haijian (Frontiers in Oncology, 2023)
Langerhans cell sarcoma (LCS) is a rare malignancy of dendritic cells and usually results in poor oncological outcomes. We present the first case of primary LCS in the urinary bladder treated by TURBT and short-term local chemotherapy. TURBT and regional chemotherapy may be a remedial method with good for patients with LCS urinary bladder.